Relationship between xylene, RQ xylene concentration and enzyme activity as indicators of heart and liver function among shoe industry workers in Surabaya. - Tualeka, Abdul Rohim; Martiana, Tri; Aziz, Mohd Yusmaidie; Thamaraikani, Tamilanban; Rosnon, Roslan; Novianti, Salsabila; Rahmawati, Pudji; Ahsan, Ahsan (F1000 Research Ltd, 2024)
Background Xylene, a common solvent in painting, printing, and shoemaking, enters the body through inhalation of vapors. Methods This observational analytic study aimed to examine the relationship between xylene concentration, xylene RQ, and liver function in industrial workers in Surabaya, especially in shoe industries. The chi-square method was utilized for data analysis. To ensure the validity and reliability of the study results, air and blood sampling procedures were implemented. Air sampling was conducted to measure xylene concentrations in the workplace environment, while blood samples were collected from workers to assess Serum Glutamic Oxaloacetic Transaminase (SGOT) and Serum Glutamic Pyruvate Transaminase (SGPT) levels. The study was conducted in five regions in Surabaya, namely Kalijudan, Ketintang, Jemursari, AUP, and Romokalisari. The population includes a total of 90 workers with 77 of them taken as samples using the accidental sampling method. Results The results show that there is a relationship between xylene concentration and Serum Glutamic Oxaloacetic Transaminase (SGOT) levels (p> 0.05); (r = 0,65) and there is no relationship between xylene concentrations and Serum Glutamic Pyruvate Transaminase (SGPT) levels (p> 0.05); (r = -0,12). There was no relationship between RQ and SGOT levels (p> 0.05) and there was no relationship between RQ and SGPT levels (p> 0.05). However, from the calculation of the prevalence ratio, workers with unsafe RQ (RQ>1) have a 7.09x greater chance of experiencing damage to SGOT levels and a 1.06x greater chance of experiencing damage to SGPT levels. Conclusions Xylene exposure (concentration & RQ) affects liver enzyme levels (SGOT/SGPT) in workers. Industries should consider providing nutritious food to aid xylene removal and stricter safety policies are needed. This study highlights the importance of a holistic approach to worker health and safety when dealing with hazardous chemicals.